What is the sum of the solutions to (x − 6)(x + 0.7) = 0 ?

A) −6.7

B) −5.3

C) 5.3

D) 6.7

Skip to content# What is the sum of the solutions to (x − 6)(x + 0.7) = 0 ? A) −6.7 B) −5.3 C) 5.3 D) 6.7

Mathematics ##
Comments (5) on “What is the sum of the solutions to (x − 6)(x + 0.7) = 0 ? A) −6.7 B) −5.3 C) 5.3 D) 6.7”

### Leave a Reply Cancel reply

What is the sum of the solutions to (x − 6)(x + 0.7) = 0 ?

A) −6.7

B) −5.3

C) 5.3

D) 6.7

Solve (x + 1/2) x (x -9) = 0 Then get x = -1/2 x = 9 =0 The final solution is x1 = -1/2 , x2 =9

[tex]5.3\\[/tex]

Step-by-step explanation:

The solutions of the given equations are

[tex](x - 6)(x + 0.7) = 0\\\\\\x - 6 = 0 ; x = 6\\x + 0.7 = 0; x = -0.7\\x = 6, 0.7\\[/tex]

Difference between the two solutions of the equation is

[tex]= 6 - (0.7)\\= 5.3\\[/tex]

The answer might be D I don’t know if I’m sure

The answer is C because you add 6 and subtract .07

5.3

Step-by-step explanation:

(x − 6)(x + 0.7) = 0

using the zero product property

x-6=0 x+.7 =0

x-6+6 = 0+6 x+.7 -.7 = 0-.7

x = 6 x= -.7

sum of the solutions

6+-.7 = 5.3